The Role of Human Papillomavirus in Head and Neck Cancers - Oliveira, Lucinei Roberto; Castilho-Fernandes, Andrielle; Pessolato, Alícia Greyce Turatti; Lira, Régia Caroline Peixoto; Oliveira-Costa, João Paulo; Chavasco, Luciana Souza; Miranda, Fabiana Alves; Pereira, Ivan de Oliveira; Soares, Edson Garcia; Ribeiro-Silva, Alfredo (IntechOpen, 2012)
None